Experimental investigations about complex non-relaxing fatigue loads for carbon-black filled natural rubber. (March 2022) - Warneboldt, I.; Marco, Y.; Charrier, P.; Hervouet, W.; Champy, C.; Raoult, I.; Le Saux, V.; Szmytka, F.
Highlights: Extensive multiaxial & uniaxial fatigue test campaign on natural rubber is provided. Observations confirm connection between lifetime reinforcement and crack features. Temperature influences relaxing and non-relaxing tests (lifetime & crack features) Critical plane predictions fail for lifetime reinforcing multiaxial configurations. Analyses of crack features & lifetimes point to a local microstructure modification. Abstract: This paper presents an extensive test campaign and analysis to better understand the fatigue behavior and the mechanisms at stake for natural rubber under complex non-relaxing loads. This database includes relaxing uniaxial tests under tension and torsion, relaxing and non-relaxing tension tests for 3 temperatures, relaxing multiaxial tension-torsion proportional tests, and non-relaxing tension-torsion multiaxial sequenced tests for different temperatures. The tests are conducted on hourglass-shaped natural rubber specimens, loaded by coupled and aligned tension and torsion actuators. Various strain ratios, uniaxial and biaxial loading sequences and critical plane orientation histories over a loading cycle are achieved. A total of 240 specimens were tested. Different temperatures are imposed to affect reinforcement and provide a comparison to previous results on crystallization. Furthermore, finite element analyses (FEA) are performed to determine first the respective local mechanical state in the specimens and then to infer the crack orientation predicted from a critical plane approach based on the maximum principal strain. Finally, the results are carefully analyzed based on three indicators: the relative improvement on fatigue lifetime, the cracks features (roughness and branching, from optical and SEM observations) and their comparison to the crack orientation predicted using the critical plane approach.